2009
DOI: 10.1121/1.3238242
|View full text |Cite
|
Sign up to set email alerts
|

Role of binaural hearing in speech intelligibility and spatial release from masking using vocoded speech

Abstract: A cochlear implant vocoder was used to evaluate relative contributions of spectral and binaural temporal fine-structure cues to speech intelligibility. In Study I, stimuli were vocoded, and then convolved through head related transfer functions ͑HRTFs͒ to remove speech temporal fine structure but preserve the binaural temporal fine-structure cues. In Study II, the order of processing was reversed to remove both speech and binaural temporal fine-structure cues. Speech reception thresholds ͑SRTs͒ were measured a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 71 publications
2
29
3
Order By: Relevance
“…However, their results are in the opposite direction to those reported here-they found that progressively coarser vocoding increased SRM in their task, which involved the identification of spondaic words against sentence maskers. This discrepancy between the two studies may reflect the fact that the targets used by Garadat et al (2009) were not confusable with the maskers, and thus task performance was not limited by IM. Consistent with this speculation, their listeners achieved extremely low thresholds even in the colocated configuration, with the group mean thresholds reported to be lower than À 20 dB TMR for unprocessed stimuli.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…However, their results are in the opposite direction to those reported here-they found that progressively coarser vocoding increased SRM in their task, which involved the identification of spondaic words against sentence maskers. This discrepancy between the two studies may reflect the fact that the targets used by Garadat et al (2009) were not confusable with the maskers, and thus task performance was not limited by IM. Consistent with this speculation, their listeners achieved extremely low thresholds even in the colocated configuration, with the group mean thresholds reported to be lower than À 20 dB TMR for unprocessed stimuli.…”
Section: Discussionmentioning
confidence: 71%
“…Thus, we strongly doubt that the measured SRM would be similar, as observed by Garadat et al (2009) and Drennan et al (2007) under their experimental conditions.…”
mentioning
confidence: 88%
“…The effect of noise vocoding on SRM was predominantly driven by the interaural correlation of the noise carriers below 1.5 kHz. On the other hand, Garadat et al (2009) conducted a similar study to Andersen et al (2010), but found that greater SRM was achieved with the TVC than without, and that there was no difference in performance between applying vocoding before or after HRIRs. However, Garadat et al (2009) only used a single masker sentence lateralized to one side, allowing the listeners to take advantage of the improved SNR at the other ear.…”
Section: Introductionmentioning
confidence: 92%
“…To the best of our knowledge, the effect of energetic and informational masking has not been systematically investigated in the same group of children using repeated measures. In future developmental studies on SRM, the effect of the energeticinformational masking spectrum should be systematically investigated to reveal the maturation of bottom-up peripheral auditory processing versus top-down central auditory executive control through the use of different numbers of talker babbles or noise-excited vocoded speech with different numbers of bands (Garadat, Litovsky, Yu, & Zeng, 2009). It is anticipated that maskers with a higher degree of informational masking could reveal a longer developmental time for SNR-50% for NS and SRM measures, as it involves more top-down central auditory executive control at the cortical level that requires a longer developmental period to reach adult performance levels.…”
Section: Energetic Versus Informational Maskers In Future Developmentmentioning
confidence: 99%